Comparative Performance Evaluation of Continuous Monitoring Blood Culture Systems Using Simulated Septic Specimen - Kwangjin Ahn; Taesic Lee; Sangwon Hwang; Dong Min Seo; Young Uh (Diagnostics)
Background/Objectives: Continuous monitoring blood culture systems (CMBCSs) are revolutionary automated instruments that facilitate the rapid identification of pathogens in blood samples from patients with sepsis. However, with only a few CMBCSs being widely used as references, user dependency on these limited options has grown. In response, a new CMBCS was developed and compared with existing systems to evaluate microbial growth. Methods: HubCentra84 was compared to BacT/Alert® 3D and BACTEC™ FX. Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Bacteroides fragilis, and Candida albicans were selected as representative clinically infectious microorganisms. Colonies from pure cultures were diluted with 0.9% saline to create simulated sepsis specimens (SSSs). The SSSs were injected into dedicated culture bottles for each instrument. Thirty paired tests were performed for each strain. Results: Colony-forming units of the added SSSs were consistent according to bacteria, and all strains demonstrated robust growth in three CMBCSs. Time-to-positivity was uniformly observed according to the instruments used. The novel CMBCS detected the growth of the clinically significant bacteria S. aureus, S. pneumoniae, E. coli, and P. aeruginosa approximately 2 h faster than the other two systems. However, it was approximately 200 min slower for C. albicans and 3000 min for B. fragilis. Conclusions: The novel CMBCS demonstrates advantages in detecting the growth of common clinical bacteria. Although slow growth was detected for certain microorganisms, it successfully captured the growth of all tested microorganisms.